SPECIES COMPOSITION OF WOLF (CANIS LUPUS) HELMINTH FAUNA IN KAZAKHSTAN - Uakhit, R.; Smagulova , A.; Lider , L.; Leont'ev , S.; Berber , A.; Kiyan , V. (Eurasian Journal of Applied Biotechnology, 2022)
The article presents data on the study of the species composition of wolf helminth fauna in the period from 2019 to 2021. A total of 39 wolves (Canis lupus) were examined, and their parasite fauna was assessed. The study identified the following types of helminths Echinococcus granulosus, Taenia krabbei, Dypilidium spp., Mesocestoides spp., Toxascaris leonina, Trichinella nativa, Dirofilaria repens. The extensiveness of the invasion wolves by helminths was relatively high in the western part region (96.5%), and towards the north-central part region, this indicator significantly decreased (65.2%). The average number of helminths was high, with some infected animals carrying several types of parasites. Thus, the intensity of invasion by helminths in wolves was 7.6 specimens per infected individual host. The research aimed to study the endoparasitic fauna of wild wolves using complex classical parasitological and molecular genetic methods. Samples of helminths were differentiated by amplification and sequencing using the marker gene cytochrome oxidase COX1 (GenBank accession number: MT877205, MZ505444, MZ669895, MZ724175). There is a need to assess the distribution of helminths in intermediate and final hosts populations and provide appropriate health education to avoid maintaining parasite life cycles and infestations, which will become a public health problem in the future.